AI-Driven Efficiency in Pharmaceutical Manufacturing: Enhancing Productivity, Compliance, and Decision-Making - Aditya Pradeep Sohoni (Information Technology and Science (ITScience), 2025)
The pharmaceutical manufacturing business exists in a strictly controlled sector needing high standards of efficiency along with precise operations and complete adherence to standards. The current manual work practices in traditional systems result in both workflow inefficiencies together with opportunities for human mistakes. Artificial Intelligence (AI) through its ChatGPT application provides modern industrial solutions that optimize workflows and automatically document processes and create decision-enhancing technology. The study investigates how AI enables pharmaceutical manufacturing operations to become more efficient as well as ensuring product quality and handling supply chains and meeting regulatory needs. Organizations achieve better productivity rates and decreased manual labor while basing decisions on data through AI-driven solutions which create enhanced compliance as well as greater manufacturing performance.